Table manners : how to behave in the modern world and why bother - Tower, Jeremiah (Farrar, Straus and Giroux, 2016)
"An authoritative and witty guide to modern table manners for all occasions by one of the world's most acclaimed chefs and restaurateurs. Table Manners is an entertaining and practical guide to manners for everyone and every occasion. Whether you are a guest at a potluck or the host of a dinner party, a patron of your local bar or an invitee at a state dinner, this book tells you exactly how to behave: what to talk about, what to wear, how to eat. Jeremiah Tower has advice on everything: food allergies, RSVPs, iPhones, running late, thank-yous, restaurant etiquette, even what to do when you are served something disgusting. With whimsical line drawings throughout, this is "Strunk and White" for the table"--